Calculus Driven Creativepreneurship as an Innovative Economic Solution for MSMEs: Kewirausahaan Kreatif Berbasis Kalkulus sebagai Solusi Ekonomi Inovatif untuk UMKM - Untung Rahardja; Ester Ananda Natalia; Qurotul Aini; Thomas Sumarsan Goh; Clara Pasha Lim (ADI Publisher, 2025)
Calculus-based creativepreneurship is an innovative approach aimed at enhancing the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) by applying mathematical concepts in business strategies. In the midst of the creative economy and digital transformation, MSMEs face challenges related to product innovation, financial management, and optimal use of digital technology. Limited access to data-driven training and quantitative analysis skills hinders effective and measurable business decision-making. This community service activity aims to bridge the gap between academic theory and field practice by integrating calculus concepts into MSME business decision-making processes. The program was conducted as part of the Raharja Enrichment Program (REP), which adopts the Outcome-Based Education (OBE) approach to provide practical, hands-on learning experiences. The method involved direct consultation with MSME actors. Students conducted observations, problem identification, and data analysis to apply calculus in calculating production costs, setting selling prices, break-even analysis and profit projections. Additionally, students used basic software tools to simulate cost and revenue scenarios and their impact on profit margins, making the learning experience more contextual and practical. The results show that the application of calculus supports MSMEs in improving operational efficiency, developing product innovation, and implementing more systematic, data driven financial strategies. Several partner MSMEs began adopting periodic performance evaluations using function graphs and rates of change. The integration of calculus in the development of creativepreneurship through REP provides dual benefits empowering MSMEs and enhancing student competencies. This model represents a strategic step toward building creative, data-based business solutions and can be replicated across various business sectors in the digital era.